2020
DOI: 10.5709/acp-0282-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cognitive and Perceptual Judgment Processes in Gymnastics Using Essential Kinematics Information

Abstract: The aim of the current study was to transfer the method of using isolated kinematics information combined with the examination of perceptual-cognitive processes to gymnastics judging and thereby investigating the informational underpinnings of skilled perception and judgment. More specifically, a combination of process-tracing methods that include both the gaze pattern (via eye tracking) and the performance judgment (via ratings on a six-point Likert scale) of participants with different gymnastics expertise (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…e design idea is to unify the scale of the high-level feature map with that of low-level feature map through upsampling and fuse the upsampled high-level feature map with the corresponding low-level feature map [18]. e top-down feature fusion method is used to fuse the two scale feature maps, and the schematic diagram is shown in Figure 3.…”
Section: Structure Design Of Top-down Feature Fusionmentioning
confidence: 99%
“…e design idea is to unify the scale of the high-level feature map with that of low-level feature map through upsampling and fuse the upsampled high-level feature map with the corresponding low-level feature map [18]. e top-down feature fusion method is used to fuse the two scale feature maps, and the schematic diagram is shown in Figure 3.…”
Section: Structure Design Of Top-down Feature Fusionmentioning
confidence: 99%
“…Based on information reduction theory [31], we expected that judges would have a certain level of specialty in evaluating the performance of figure skating jumps and, therefore, the judge group would have a longer fixation duration. Prior studies have indicated mixed results, with certain case studies reporting a longer fixation duration for skaters [26] and others reporting no differences by subject attributes [27]. In addition, Pizzera et al reported no difference in the fixation duration between judges with and without specific motor experience [24].…”
Section: Number Of Fixationsmentioning
confidence: 99%
“…However, there were no significant differences in fixation time or number of fixations among the three types of specialties. Notably, the visual specialist group included both referees and coaches [27].…”
Section: Eye Movements Of Sports Judges Research In Sports Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, a disadvantage of test outcomes as reference is that for many exercises in physical education, no tests exist. An alternative approach, therefore, is to utilise trainers who hold a sufficiently high level of judgment accuracy with regard to the studied exercise as reference (Bläsing, 2015;Mack, 2020;Newberry et al, 2021;Stadler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%